Adaptive 3D ray tracing approach for indoor radio signal prediction at 3.5 GHz - Mohd Nazeri Kamaruddin; Tan Kim Geok; Omar Abdul Aziz; Tharek Abd Rahman; Ferdous Hossain; Azlan Abdul Aziz (Institute of Advanced Engineering and Science, 2022)
This paper explained an adaptive ray tracing technique in modelling indoor radio wave propagation. As compared with conventional ray tracing approach, the presented ray tracing approach offers an optimized method to trace the travelling radio signal by introducing flexibility and adaptive features in ray launching algorithm in modelling the radio wave for indoor scenarios. The simulation result was compared with measurements data for verification. By analyzing the results, the proposed adaptive technique showed a better improvement in simulation time, power level and coverage in modelling the radio wave propagation for indoor scenario and may benefit in the development of signal propagation simulators for future technologies.